Catalyst carrier as well as preparation method and application thereof

By adding glue solvent and modification additives to the preparation process of the catalyst support, combined with the molding, drying and calcining steps, the problem of insufficient mechanical strength of the catalyst support is solved, and a carrier preparation with high specific surface area, pore volume and mechanical strength is achieved, which improves the thermal stability and resistance to carbon deposits of the catalyst.

CN119909665AActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311436536.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

The existing large-particle catalyst support is insufficient mechanical strength, which leads to the catalyst being easily broken and has poor thermal stability and resistance to carbon deposits.

Method used

By mixing the carrier precursor with a gel solvent and a modification additive, molding, drying and calcining, a catalyst support with high specific surface area, pore volume and mechanical strength was prepared.

Benefits of technology

The prepared catalyst support has a large specific surface area and pore volume, high average mechanical strength, and concentrated mechanical strength distribution of the support, which improves the thermal stability and resistance to carbon deposits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909665A_ABST
    Figure CN119909665A_ABST
Patent Text Reader

Abstract

The invention relates to the field of carrier preparation, and discloses a catalyst carrier and a preparation method and application thereof, the specific surface area of the catalyst carrier is 20-200m < 2 > / g, and the pore volume is 0.1-0.7 mL / g; the average mechanical strength of the catalyst carrier is 18-110 N / mm; the particle mechanical strength dispersion coefficient of the catalyst carrier is in the range of 0-0.6. The catalyst carrier has large specific surface area and pore volume, high average mechanical strength and concentrated mechanical strength distribution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carrier preparation, and in particular to a catalyst carrier and a preparation method and application thereof. Background Art

[0002] In reactions such as catalytic oxidation, steam reforming, dry reforming, and medium-temperature and high-temperature methanation, there are problems such as high reaction temperature, large heat flux, easy carbon deposition, and harsh hydrothermal environment. The catalysts used in these scenarios are not only required to have high catalytic performance, but also have high requirements on the thermal stability, hydrothermal stability, anti-carbon deposition performance and mechanical strength of the catalysts.

[0003] The shape of the catalyst affects the strength, activity, resistance and airflow distribution of the catalyst, and is one of the important properties of the catalyst. Existing catalysts have various shapes. The conversion catalysts are wheel-shaped and porous plate-shaped, which not only increase the surface area and activity, but also ensure the strength of the catalyst and reduce the airflow resistance. In order to further increase the surface area of ​​such catalysts, the ribs and walls of the special-shaped catalysts can be thinner, but this leads to a decrease in the mechanical strength of the catalyst and makes it easy to break. Once the catalyst is broken, the particles are small, which can easily cause a sharp increase in resistance.

[0004] In order to better exert the performance of the catalyst, in addition to requiring better physical and chemical indicators of the carrier (usually requiring a larger specific surface area, a larger pore volume, a more suitable pore size and surface properties, higher strength, etc.), the shape of the catalyst also plays a very important role in engineering applications (heat transfer, mass transfer, pressure drop, etc.). The commonly used alumina shapes in industry are mainly strip, column, ring, honeycomb and spherical. Extrusion molding is an efficient and relatively low-cost molding method. The fixed bed has requirements for the catalyst particle size. In order to reduce the pressure drop, the catalyst particle size and particle shape have certain requirements so that the catalyst bed has a higher porosity after filling and the pressure drop is reduced. It is easier to obtain a carrier of general strength by extruding a material with a smaller particle diameter using extrusion molding, but it is difficult to obtain a high-strength carrier when extruding a larger particle diameter.

[0005] Existing larger particle carriers are difficult to balance mechanical strength, specific surface area and pore structure stability. There is an urgent need to develop a catalyst carrier that has high mechanical strength, high specific surface area and high pore volume. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem in the prior art that large-particle catalyst carriers have insufficient mechanical strength, which makes the prepared catalyst easy to break and has poor thermal stability and anti-carbon deposition ability, and to provide a catalyst carrier and a preparation method and application thereof. The catalyst carrier has a large specific surface area and pore volume, high average mechanical strength, and a concentrated distribution of the mechanical strength of the carrier.

[0007] In order to achieve the above object, the present invention provides a catalyst carrier in the first aspect, wherein the specific surface area of ​​the catalyst carrier is 20-200m 2 / g, pore volume is 0.1-0.7mL / g;

[0008] The average mechanical strength of the catalyst carrier is 18-110N / mm;

[0009] The particle mechanical strength dispersion coefficient of the catalyst carrier is in the range of 0-0.6.

[0010] A second aspect of the present invention provides a method for preparing a catalyst carrier, wherein the method comprises the following steps:

[0011] The carrier precursor is mixed with a peptizing agent and a modification aid, and then molded, dried and calcined to obtain a catalyst carrier;

[0012] Wherein, the temperature change of the material before and after molding is less than 20°C;

[0013] The modification aid is selected from at least one of compounds containing alkali metal elements, alkaline earth metal elements and rare earth metal elements.

[0014] The third aspect of the present invention provides a catalyst carrier prepared by the preparation method described in the second aspect.

[0015] The fourth aspect of the present invention provides an application of the catalyst carrier described in the first aspect or the third aspect in the field of catalyst preparation.

[0016] Through the above technical solution, the beneficial effects obtained are as follows:

[0017] (1) The catalyst carrier provided by the present invention has a large specific surface area and pore volume, a high average mechanical strength, and a concentrated distribution of the mechanical strength of the carrier;

[0018] (2) In the present invention, in the process of preparing the catalyst carrier, the addition of a modifying aid combined with the molding conditions and the control of the temperature change of the material before and after molding can further improve the average mechanical strength of the prepared catalyst carrier. The catalyst carrier is conducive to the loading and dispersion of the active components. The prepared carrier has a large specific surface area and pore volume while ensuring that the mechanical strength distribution of the carrier is concentrated. The preparation method is simple and stable to operate, easy to scale up industrially, has strong adaptability to raw materials, and is environmentally friendly. The catalyst prepared using the above-mentioned carrier has high catalytic activity and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is an appearance diagram of the butterfly-shaped extruded strip obtained in Example 1;

[0020] Figure 2Schematic diagram of mechanical strength distribution of catalyst supports of Example 2, Example 6 and Comparative Example 3;

[0021] Figure 3 is an appearance diagram of the Raschig ring extruded strip obtained in Example 11;

[0022] Figure 4 IR spectra of the extruded strips of Example 6 and Comparative Example 3. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] The first aspect of the present invention provides a catalyst carrier, wherein the specific surface area of ​​the catalyst carrier is 20-200m 2 / g, pore volume is 0.1-0.7mL / g;

[0025] The average mechanical strength of the catalyst carrier is 18-110N / mm;

[0026] The particle mechanical strength dispersion coefficient of the catalyst carrier is in the range of 0-0.6.

[0027] In the present invention, the catalyst carrier has a high specific surface area and a high pore volume, and can ensure a high average mechanical strength at the same time, and the mechanical strength distribution of the carrier is concentrated.

[0028] In the present invention, the discrete coefficient refers to the dispersion of mechanical strength of catalyst carrier particles, which is the ratio of the standard deviation of the mechanical strength values ​​of a group of catalyst carrier particles to their average value. The number of particles of the catalyst carrier is n, n is 15-30, and the discrete coefficient of mechanical strength of the catalyst carrier particles is in the range of 0-0.6.

[0029] According to the present invention, preferably, the catalyst carrier particle mechanical strength dispersion coefficient is in the range of 0-0.6, for example, 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, or any range between two thereof, preferably in the range of 0-0.55.

[0030] In the present invention, the average mechanical strength refers to the average value calculated from the compressive strength of 22 catalyst carrier particles tested. The compressive strength is measured by measuring the side crushing mechanical strength.

[0031] According to the present invention, preferably, the average mechanical strength of the catalyst carrier is 18-110N / mm, for example, 18N / mm, 20N / mm, 22N / mm, 24N / mm, 28N / mm, 32N / mm, 36N / mm, 40N / mm, 48N / mm, 56N / mm, 60N / mm, 70N / mm, 80N / mm, 90N / mm, 100N / mm, 110N / mm, or any range therebetween, preferably 20-100N / mm, more preferably 30-80N / mm.

[0032] According to the present invention, the type of the catalyst carrier is not particularly limited, and the specific surface area, pore volume and average mechanical strength of the carrier can meet the limited range. Preferably, the catalyst carrier is selected from at least one of aluminum oxide, silicon dioxide, zirconium oxide, titanium dioxide, magnesium oxide, calcium oxide, zinc oxide, silicon nitride, silicon carbide and carbon materials, preferably aluminum oxide. In the present invention, preferably, the mass percentage of aluminum oxide in the catalyst carrier is not less than 60wt%, preferably 65-98wt%.

[0033] According to the present invention, preferably, the specific surface area of ​​the catalyst carrier is 20-200m 2 / g, for example 20m 2 / g, 25m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g, 60m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 110m 2 / g, 120m 2 / g, 140m 2 / g, 160m 2 / g, 180m 2 / g, 200m 2 / g, or any range between the two, preferably 25-190m 2 / g.

[0034] According to the present invention, preferably, the pore volume of the catalyst support is 0.1-0.7mL / g, such as 0.1mL / g, 0.15mL / g, 0.2mL / g, 0.25mL / g, 0.3mL / g, 0.35mL / g, 0.4mL / g, 0.45mL / g, 0.5mL / g, 0.55mL / g, 0.6mL / g, 0.65mL / g, 0.7mL / g, or any range between the two, preferably 0.2-0.65mL / g. In the present invention, the specific surface area and pore volume of the catalyst support are measured by BET low temperature nitrogen adsorption method.

[0035] According to the present invention, the particle diameter of the catalyst carrier is not particularly limited. Preferably, the particle diameter of the catalyst carrier is 3-20 mm, preferably 3.5-17 mm. It is easier to obtain high mechanical strength by molding a catalyst carrier with a smaller particle diameter. The larger the particle diameter of the catalyst carrier, the more difficult it is to improve the mechanical strength. In the present invention, the catalyst carrier has a large particle diameter while ensuring a high specific surface area, a high pore volume and a high mechanical strength.

[0036] In the present invention, the particle diameter of the catalyst carrier is measured by measuring the diameter of the circumscribed circle of the carrier cross section.

[0037] The catalyst carrier material provided by the present invention has high mechanical strength, and the carrier shape can be changed and selected in various ways, which can increase the catalyst surface area, reduce airflow resistance, and thus improve catalyst performance and reduce plant operation energy consumption and cost.

[0038] A second aspect of the present invention provides a method for preparing a catalyst carrier, wherein the method comprises the following steps:

[0039] The carrier precursor is mixed with a peptizing agent and a modification aid, and then molded, dried and calcined to obtain a catalyst carrier;

[0040] Wherein, the temperature change of the material before and after molding is less than 20°C;

[0041] The modification aid is selected from at least one of compounds containing alkali metal elements, alkaline earth metal elements and rare earth metal elements.

[0042] In the present invention, the molding temperature is controlled within a relatively low temperature range to avoid molding at a relatively high temperature, which will cause uneven heating of the outer surface and the inner part of the particles of the molded product, excessively high outer surface temperature and excessively low inner temperature, thereby reducing the mechanical strength of the obtained catalyst carrier. The preparation method is simple and stable to operate, easy to industrially scale up, has strong raw material adaptability, and is environmentally friendly.

[0043] According to the present invention, preferably, the temperature change of the material before and after molding is less than 20°C, preferably less than 18°C, and more preferably less than 10°C. In the present invention, the temperature change of the material before and after molding is controlled to be small, so that the material is heated evenly during the molding process, which helps to improve the average mechanical strength of the catalyst carrier. In the present invention, when the catalyst carrier is prepared by multiple moldings, the temperature change of the material before and after molding refers to the temperature change of the material before and after the last molding.

[0044] According to the present invention, preferably, the mixing includes dry mixing, kneading and / or mixing rolling. Preferably, the conditions of the kneading and / or mixing rolling include: the time of kneading and / or mixing rolling is 5-180 minutes, preferably 20-160 minutes.

[0045] According to the present invention, preferably, the molding conditions include: a molding temperature of 1-60° C., preferably 5-50° C.; and a molding pressure of 3-20 MPa, preferably 4-15 MPa.

[0046] According to a preferred embodiment of the present invention, the mixing process comprises: dry mixing the carrier precursor with the modification aid oxide, the optional extrusion aid, the optional binder and the optional lubricant for a certain period of time, and then adding an aqueous solution containing the modification aid and the peptizing agent, and mixing the above raw materials uniformly by kneading and / or mixing.

[0047] In the present invention, the modification aid is an aid that can adjust the physical properties of the carrier and increase the alkalinity of the carrier. The modification aid can be directly added to the carrier precursor in the form of a metal oxide, or dissolved in water in the form of a metal compound and then added to the carrier precursor, or added to the catalyst carrier by impregnation. The inventors of the present invention have found that by adding a peptizing agent and a suitable modification aid combined with molding conditions during molding, a high-strength carrier with a large specific surface area and pore volume can be obtained.

[0048] According to the present invention, preferably, the modification aid is selected from at least one of compounds containing alkali metal elements, alkaline earth metal elements, transition metal elements and rare earth metal elements, and is preferably selected from at least one of oxides, acetates, nitrates, hydroxides, carbonates and basic carbonates of alkali metal elements, alkaline earth metal elements, transition metal elements and rare earth metal elements.

[0049] According to the present invention, preferably, the modification aid is selected from at least one of nitrates, oxides and acetates of alkali metal elements, alkaline earth metal elements and rare earth metal elements, preferably selected from at least one of lanthanum nitrate, magnesium nitrate, zinc nitrate, potassium nitrate, magnesium oxide, calcium oxide, lanthanum acetate and magnesium acetate.

[0050] In the present invention, preferably, the carrier and the modifying aid are of different material types.

[0051] According to the present invention, preferably, relative to 100 parts by weight of the carrier precursor, the amount of the modification aid added is 0.6-15 parts by weight, such as 0.6 parts by weight, 0.8 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 6 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight, 15 parts by weight, or any range between the two, preferably 0.8-12 parts by weight. Too little modification aid added cannot achieve the effect of adjusting the physical properties of the carrier and increasing the alkalinity of the carrier; too much modification aid added affects the mechanical strength of the catalyst carrier and reduces the specific surface area of ​​the carrier.

[0052] According to the present invention, preferably, the process of adding water is further included after adding the modification aid. Based on the weight of the carrier precursor being 1 g, the volume of water added is 0.5-1.5 mL, preferably 0.65-1.2 mL.

[0053] According to the present invention, preferably, the carrier precursor is a substance that is converted into a carrier by subsequent calcination. In the present invention, there is no particular limitation on the source of the carrier precursor, and those skilled in the art can select a conventional carrier precursor, which can be commercially available or prepared by an existing method, and can be converted into a carrier after calcination.

[0054] In the present invention, preferably, the carrier precursor is selected from at least one of alumina, metal aluminates, silicon dioxide, aluminosilicates, silicate minerals, titanium dioxide, zirconium oxide, magnesium oxide, zinc oxide, silicon nitride, silicon carbide and carbon materials. The alumina may be hydrated alumina and / or alumina colloid, and the aluminosilicate may be zeolite and / or kaolin.

[0055] According to the present invention, preferably, the carrier precursor is selected from at least one of pseudo-boehmite, calcium oxide and magnesium oxide.

[0056] According to the present invention, preferably, the carrier is selected from at least one of aluminum oxide, silicon dioxide, zirconium oxide, titanium dioxide, magnesium oxide, calcium oxide, zinc oxide, silicon nitride, silicon carbide, and carbon materials.

[0057] In the present invention, preferably, alumina has the characteristics of large specific surface area, controllable pore structure, good thermal stability and strong adsorption capacity. Pseudo-boehmite is used as a carrier precursor to prepare the carrier. The prepared catalyst carrier has a higher specific surface area and pore volume, which is beneficial to the loading and dispersion of the active components, and the further prepared catalyst has a higher catalytic activity.

[0058] According to the present invention, preferably, the peptizing agent is an organic acid and / or an inorganic acid, preferably selected from at least one of nitric acid, aluminum nitrate, acetic acid and citric acid, more preferably a mixture of nitric acid and aluminum nitrate and / or citric acid. In the present invention, the addition of a peptizing agent can make the carrier precursor particles fully peptized, improve the mechanical strength of the formed catalyst carrier, and improve the pore structure. In the present invention, the type of the peptizing agent is not particularly limited, and can be various peptizing agents conventionally used in the art.

[0059] According to the present invention, preferably, relative to 100 parts by weight of the carrier precursor, the amount of the peptizing agent added is 0.4-10 parts by weight, preferably 0.6-8 parts by weight. In the present invention, the amount of the peptizing agent added is controlled within the above range to avoid adding too little peptizing agent, which may result in insufficient peptization of the obtained catalyst carrier, and adding too much peptizing agent, which may result in excessive acidity of the catalyst carrier and weakened mechanical strength.

[0060] In the present invention, the modification aid is used in combination with the carrier precursor and the peptizing agent to improve the stability of the carrier precursor, so that the carrier precursor is not prone to phase transition after calcination, which helps to increase the specific surface area and pore volume of the catalyst carrier without affecting the mechanical strength.

[0061] According to the present invention, preferably, the mixing further includes adding an optional extrusion aid, an optional binder and an optional lubricant.

[0062] In the present invention, unless otherwise specified, the term "optional" means containing or not containing, adding or not adding, using or not using. Specifically, the present invention may add an extrusion aid or not add an extrusion aid. There is no particular limitation on the manner of adding each additive, and the additives may be added separately or together.

[0063] According to the present invention, the type of the extrusion aid is not particularly limited, and can be a conventional extrusion aid in the art, preferably sesbania powder and / or cellulose. The amount of the extrusion aid is not particularly limited, and those skilled in the art can make adaptive adjustments as needed to ensure that subsequent molding is carried out smoothly. Preferably, relative to 100 parts by weight of the carrier precursor, the addition amount of the extrusion aid is 0-8 parts by weight, preferably 0-6 parts by weight.

[0064] In the present invention, preferably, the binder is an inorganic binder and / or an organic binder. The binder can play a role in binding the carrier precursor particles.

[0065] In the present invention, the type of the inorganic binder is not particularly limited, and can be any conventional inorganic binder in the art. Preferably, the inorganic binder is selected from at least one of cement, aluminum sol, silica sol, zirconium sol and titanium sol.

[0066] In the present invention, the type of the organic binder is not particularly limited, and can be any conventional organic binder in the art. Preferably, the organic binder is selected from at least one of methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose and microcrystalline cellulose.

[0067] According to the present invention, the amount of the binder is not particularly limited, and those skilled in the art can adaptably choose whether to add the binder and the amount of the binder according to the mixing situation. Preferably, the amount of the binder added is 0-4 parts by weight, preferably 0-3 parts by weight, relative to 100 parts by weight of the carrier precursor.

[0068] According to the present invention, the type of the lubricant is not particularly limited, and can be a conventional lubricant in the art. Those skilled in the art can select the type and amount of the lubricant according to the adaptability of the molding effect. Preferably, the lubricant is selected from at least one of glycerol, polyol, polyester, magnesium stearate, stearic acid, talc and graphite.

[0069] According to the present invention, preferably, the amount of the lubricant added is 0-10 parts by weight, preferably 0-5 parts by weight, relative to 100 parts by weight of the carrier precursor. In the present invention, the addition of the lubricant has a lubricating effect, which helps the smooth molding and can improve the average mechanical strength of the catalyst carrier in accordance with the molding conditions.

[0070] According to a preferred embodiment of the present invention, the mixing process comprises: dry mixing the carrier precursor with the modification aid oxide, the optional extrusion aid, the optional binder and the optional lubricant for a certain period of time, and then adding an aqueous solution containing the modification aid and the peptizing agent, and mixing the above raw materials uniformly by kneading and / or mixing.

[0071] In the present invention, preferably, the weight ratio of the total mass of water added during the mixing process to the carrier precursor is 0.5-2.5:1, preferably 0.6-2:1, and more preferably 0.65-1.6:1.

[0072] According to a preferred embodiment of the present invention, the molding method is selected from at least one of extrusion molding, compression molding and ball rolling molding. Those skilled in the art can select conventional molding equipment to perform the molding.

[0073] In the present invention, preferably, the extrusion molding method is adopted to produce a catalyst carrier having a higher specific surface area and pore volume and a higher mechanical strength, and has a higher preparation efficiency.

[0074] In the present invention, the shape of the product obtained by extrusion molding is not particularly limited. Preferably, it is selected from at least one of butterfly, cylindrical, clover, honeycomb, Raschig ring and porous special shape. In the present invention, the shape of the molded product is preferably Raschig ring and / or butterfly, which has better thermal conductivity, so that the catalyst carrier is heated more evenly during the molding process.

[0075] In the present invention, the material before molding also includes mixing the unqualified material that has been molded with water, mixing evenly by kneading and / or mixing and grinding, and then performing final molding. In the present invention, by mixing the molded product again, it is helpful to improve the product qualification rate. The unqualified material refers to the undried molded strips with rough surface, incomplete shape and average mechanical strength of less than 20N / mm after random inspection and roasting.

[0076] In the present invention, preferably, the shaped product is dried before calcining, and the drying conditions are not particularly limited, and those skilled in the art can select conventional drying methods and drying conditions. Preferably, the drying conditions include: a drying temperature of 30-180°C, preferably 45-160°C, more preferably 70-140°C; a drying time of 0.5-100 hours, preferably 1-80 hours, more preferably 2-70 hours.

[0077] According to a preferred embodiment of the present invention, the drying process comprises: drying at 30-70° C. for 2-50 hours, and then drying at 100-150° C. for 2-20 hours.

[0078] According to the present invention, preferably, the calcination conditions include: calcination temperature of 700-1350°C, preferably 750-1250°C; calcination time of 1-8 hours, preferably 2-6 hours; heating rate of 1-8°C / min, preferably 2-6°C / min. In the present invention, high temperature calcination is carried out under the above conditions, and the obtained catalyst carrier has a higher specific surface area.

[0079] The third aspect of the present invention provides a catalyst carrier prepared by the preparation method described in the second aspect.

[0080] The catalyst carrier prepared by the method for preparing a catalyst carrier according to the present invention has an increased specific surface area and pore volume, which is beneficial to the loading and dispersion of active components, so that the catalyst prepared using the carrier provided by the present invention has higher catalytic activity and selectivity.

[0081] The fourth aspect of the present invention provides an application of the catalyst carrier described in the first aspect or the third aspect in the field of catalyst preparation.

[0082] In the present invention, the catalyst carrier is prepared by loading the catalytic active component by a conventional method in the field of catalyst preparation, and the method selects at least one of metal vapor deposition method, coating method, impregnation method, infiltration method, catalytic active composition precipitation method, disk coating method and slurry impregnation (dip coating) method. The impregnation method, precipitation method and disk coating method are suitable for preparing catalysts whose active components are soluble metal compounds, including at least one of metal nitrates, metal halides, metal carboxylates and metal sulfates. The slurry impregnation method is suitable for preparing catalysts whose active components are insoluble metal compounds, including metals and / or metal oxides.

[0083] In the present invention, the metal element in the catalyst active component is at least one selected from alkali metal elements, alkaline earth metal elements, transition metal elements, rare earth metal elements and noble metal elements.

[0084] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, unless otherwise specified, all reagents used are commercially available;

[0085] The screw extruder was purchased from the Science and Technology Industry General Factory of South China University of Technology, model F-26;

[0086] The test methods and test conditions for the specific surface area, pore volume, particle diameter and average mechanical strength of the catalyst carrier are described in the aforementioned specification and will not be repeated here.

[0087] Example 1

[0088] (1) Prepare a peptizing agent solution by weighing 2 g of citric acid and 6 g of lanthanum nitrate, adding 156 mL of water and 1.6 g of nitric acid with a mass concentration of 63%, and stirring to dissolve.

[0089] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder were dry mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and the mixture was kneaded for 10 min, mixed and rolled for 40 min to mix evenly, and then 4 mm butterfly strips were extruded on a screw extruder, and the molding temperature was controlled to be 45°C and the molding pressure was 6.5 MPa to obtain a molded product. The material temperature change before and after molding was 11°C. The molded product prepared above was dried at 120°C for 4 hours and calcined at 960°C for 4 hours, with a heating rate of 4°C / min, to obtain a catalyst carrier A1. Figure 1 This is the appearance of the butterfly-shaped extruded strip prepared in Example 1.

[0090] Comparative Example 1

[0091] The catalyst carrier was prepared according to the method of Example 1, except that the dry mixing time was 2 minutes and the mixing and grinding time was 10 minutes. The catalyst carrier was then molded according to the method of Example 1, the molding conditions were controlled to be consistent, and then dried and calcined to obtain the catalyst carrier D1.

[0092] Comparative Example 2

[0093] A catalyst carrier was prepared according to the method of Example 1, except that the temperature change before and after molding in step (2) was 30° C., to obtain a catalyst carrier D2.

[0094] Example 2

[0095] (1) Prepare a peptizing agent solution by weighing 3 g of citric acid, 2 g of zinc nitrate, and 2 g of potassium nitrate, adding 166 mL of water and 1.6 g of nitric acid with a mass concentration of 63%, and stirring to dissolve.

[0096] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder were dry mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and the mixture was kneaded for 20 min, mixed and rolled for 40 min to mix evenly, and then 4 mm butterfly strips were extruded on a screw extruder, and the molding temperature was controlled to be 50°C and the molding pressure was 6 MPa to obtain a molded product. The material temperature change before and after molding was 11°C. The molded product prepared above was dried at 120°C for 4 hours and calcined at 960°C for 4 hours, with a heating rate of 4°C / min, to obtain a catalyst carrier A2.

[0097] Example 3

[0098] (1) Prepare a peptizing agent solution by weighing 11.12 g aluminum nitrate and 5 g magnesium nitrate, adding 165 mL water, and stirring to dissolve.

[0099] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder were dry mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and the mixture was kneaded for 20 min and mixed for 50 min; the obtained material was extruded into 4 mm butterfly strips on a screw extruder. The molding temperature was controlled to be 45°C and the molding pressure was 8 MPa to obtain a molded product. The temperature change of the material before and after molding was 7°C. The molded product prepared above was dried at 120°C for 4 hours and calcined at 1000°C for 4 hours with a heating rate of 4°C / min to obtain a catalyst carrier A3.

[0100] Example 4

[0101] (1) Prepare a peptizing agent solution by weighing 2.4 g of nitric acid with a mass concentration of 63%, adding 4 g of glycerol, 2 g of potassium nitrate and 6 g of lanthanum nitrate, adding 164 mL of water, and stirring to dissolve.

[0102] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder were uniformly mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, the above mixture was kneaded for 20 min, mixed and rolled for 50 min, and 4 mm X-shaped strips were extruded on a screw extruder. The molding temperature was controlled to be 35° C. and the molding pressure was 8.5 MPa to obtain a molded product. The material temperature change before and after molding was 7° C. The molded product prepared above was dried at 100° C. for 4 hours and calcined at 960° C. for 4 hours at a heating rate of 4° C. / min to obtain a catalyst carrier A4.

[0103] Example 5

[0104] (1) Prepare a peptizing agent solution by weighing 2.4 g of nitric acid with a mass concentration of 63%, adding 6 g of a modification aid lanthanum nitrate, adding 162 mL of water, and stirring to dissolve.

[0105] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 10 g of sesbania powder, 5 g of modified auxiliary calcium oxide, and 2 g of methyl cellulose were uniformly mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder. The above mixture was kneaded for 80 min to mix evenly, and 4 mm butterfly strips were extruded on a plunger extruder. The molding temperature was controlled to be 45°C and the molding pressure was 9 MPa to obtain a molded product. The material temperature change before and after molding was 8°C. The above molded product was dried at 120°C for 4 hours and calcined at 1000°C for 4 hours at a heating rate of 3°C / min to obtain a catalyst carrier A5.

[0106] Example 6

[0107] (1) Prepare a peptizing agent solution by weighing 2.4 g of nitric acid with a mass concentration of 63%, adding 6 g of lanthanum nitrate, and adding 156 mL of water to stir and dissolve.

[0108] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder, 7 g of modified auxiliary magnesium oxide, and 4 g of methyl cellulose were uniformly mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder. The above mixture was kneaded for 5 min, and then the above mixture was mixed and rolled for 90 min to mix evenly, and 4 mm butterfly strips were extruded on a plunger extruder. The molding temperature was controlled to be 40°C and the molding pressure was 10 MPa to obtain a molded product. The material temperature change before and after molding was 9°C. The above molded product was dried at 120°C for 4 hours and calcined at 1000°C for 4 hours with a heating rate of 3°C / min to obtain a catalyst carrier A6.

[0109] Comparative Example 3

[0110] A catalyst carrier was prepared according to the method of Example 6, except that the mixing and grinding was performed for 20 minutes, the molding temperature was 35°C, the temperature change before and after molding was 6°C, and the molding pressure was 3.5 MPa, to obtain a catalyst carrier D3.

[0111] Comparative Example 4

[0112] The catalyst carrier was prepared according to the method of Example 6, except that the amount of nitric acid added was 4 g, the molding temperature was 55°C, the temperature change before and after molding was 16°C, and the molding pressure was 12.5 MPa. Catalyst carrier D4 was obtained. Due to the high pressure, the orifice plate was damaged and the appearance of some extruded strips changed.

[0113] Example 7

[0114] The unqualified extruded strips after molding in Comparative Example 1 were supplemented with 10 g of water and mixed and milled for 40 minutes. The obtained material was molded and dried and calcined according to the conditions of Example 1 to obtain catalyst carrier A7.

[0115] Example 8

[0116] (1) Prepare a peptizing agent solution by adding 11.12 g of aluminum nitrate into 150 mL of water and dissolving the mixture.

[0117] (2) 200g of pseudo-boehmite powder (purchased from Sasol) and 6g of sesbania powder, 6g of magnesium oxide, and 2g of calcium oxide were mixed for 10 minutes, and then the prepared peptizing agent solution was added to the dry powder, and then the above mixture was kneaded for 30 minutes, mixed and rolled for 70 minutes to mix evenly, and extruded on a plunger extruder to form Raschig rings with an outer diameter of 6 mm and a wall thickness of 2 mm. The molding temperature was controlled to be 35°C and the molding pressure was 5MPa to obtain a molded product. The material temperature change before and after molding was 6°C. The above-prepared molded product was placed at room temperature for 24 hours, dried at 90°C for 4 hours, and calcined at 1000°C for 4 hours. The heating rate was 2°C / min to obtain a catalyst carrier A8.

[0118] Example 9

[0119] (1) Prepare a peptizing agent solution by weighing 2.4 g of nitric acid with a mass concentration of 63%, 2 g of citric acid, adding 6 g of lanthanum nitrate, and adding 168 mL of water, stirring to dissolve.

[0120] (2) 200 g of pseudo-boehmite powder (purchased from Sasol) and 6 g of sesbania powder, 6 g of magnesium oxide, and 2 g of methyl cellulose were uniformly mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and the above mixture was kneaded for 30 min, mixed and rolled for 90 min to mix evenly, and 6 mm butterfly strips were extruded on a plunger extruder. The molding temperature was controlled to be 30°C and the molding pressure was 6.8 MPa to obtain a molded product. The material temperature change before and after molding was 6°C. The molded product was placed at room temperature for 48 hours, dried at 90°C for 4 hours, and calcined at 1000°C for 4 hours. The heating rate was 2°C / min to obtain a catalyst carrier A9.

[0121] Example 10

[0122] (1) Prepare a peptizing agent solution by weighing 6 g of nitric acid with a mass concentration of 63%, adding 6 g of lanthanum nitrate, adding 210 mL of water, and stirring to dissolve.

[0123] Mix 200g of carbonized pseudo-boehmite powder (dry basis 0.7) and 6g of sesbania powder for 10 minutes, then add the prepared peptizing agent solution to the dry powder, knead the mixture for 30 minutes, mix and grind for 80 minutes to mix evenly, and extrude the obtained material on a plunger extruder to form a six-tooth bar with an outer circle diameter of 6mm and a cylindrical hole with a diameter of 1mm. Control the molding temperature to 20°C and the molding pressure to 7MPa to obtain a molded product. The temperature change of the material before and after molding is 8°C. Dry the above molded product at 60°C for 24 hours, and roast the dried bar at 960°C for 4 hours at a heating rate of 2°C / min to obtain a catalyst carrier A10.

[0124] Embodiment 11

[0125] (1) Prepare a peptizing agent solution by weighing 3 g of citric acid, 2 g of lanthanum nitrate, and 2 g of cerium nitrate, adding 166 mL of water and 1.6 g of nitric acid with a mass concentration of 63%, and stirring to dissolve.

[0126] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder were dry mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and the mixture was kneaded for 20 min, mixed and rolled for 60 min to mix evenly, and then extruded on a plunger extruder Raschig ring strips with an outer diameter of 4 mm and a wall thickness of 1.5 mm, and the molding temperature was controlled to be 50°C and the molding pressure to be 8 MPa to obtain a molded product. The material temperature change before and after molding was 11°C. The molded product was dried at 60°C for 24 hours and calcined at 1050°C for 4 hours at a heating rate of 4°C / min to obtain a catalyst carrier A11. Figure 3 This is the particle appearance picture of the catalyst carrier A11 prepared in Example 11.

[0127] Example 12

[0128] (1) Prepare a peptizing agent solution by weighing 3 g of citric acid, 2 g of lanthanum nitrate, and 2 g of cerium nitrate, adding 166 mL of water and 1.6 g of nitric acid with a mass concentration of 63%, and stirring to dissolve.

[0129] (2) 200 g of pseudo-boehmite powder (purchased from Sasol, dry basis 0.75) and 6 g of sesbania powder were dry mixed for 10 min, and then the prepared peptizing agent solution was added to the dry powder, and the mixture was kneaded for 20 min, mixed and rolled for 60 min to mix evenly, and then extruded on a plunger extruder to form a honeycomb strip with a diameter of 5 mm, a wall thickness of 1.8 mm, an internal through-hole wall thickness of 0.4 mm, and a through-hole spacing of 0.4 mm. The molding temperature was controlled to be 50°C and the molding pressure was 8 MPa to obtain a molded product. The material temperature change before and after molding was 6°C. The above molded product was dried at 60°C for 36 hours and calcined at 1050°C for 4 hours at a heating rate of 4°C / min to obtain a catalyst carrier A12.

[0130] Test Case

[0131] The test results of the specific surface area, pore volume and average mechanical strength of the prepared catalyst carrier are shown in Table 1. The dispersion coefficient is calculated by taking 22 particles of each group of catalyst carrier particles.

[0132] Table 1

[0133]

[0134]

[0135] It can be seen from Table 1 that the catalyst supports prepared in Examples 1-12 have significantly improved mechanical strength compared to Comparative Examples 1 and 2. It can be seen that the method for preparing a catalyst support provided by the present invention has a higher specific surface area and mechanical strength.

[0136] Figure 2 is a schematic diagram of the mechanical strength distribution of the carriers of Example 2, Example 6 and Comparative Example 3, from Figure 2 It can be seen that the method for preparing a catalyst carrier provided by the present invention not only has high mechanical strength, but also has low strength dispersion, which is beneficial for the catalyst to maintain stable mechanical strength during application and improve practicality. Figure 4 The infrared spectra of the extruded strips of Example 6 and Comparative Example 3 are shown in FIG. Figure 4 It can be seen that the carrier precursor after molding in Example 6 has a larger aluminum-oxygen bond signal, indicating that the molding conditions are conducive to the formation of the bond and are the intrinsic reason for the improvement of mechanical strength.

[0137] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst carrier, characterized in that The specific surface area of ​​the catalyst carrier is 20-200m 2 / g, pore volume is 0.1-0.7mL / g; The average mechanical strength of the catalyst carrier is 18-110N / mm; The particle mechanical strength dispersion coefficient of the catalyst carrier is in the range of 0-0.

6.

2. The catalyst carrier according to claim 1, wherein The catalyst carrier is selected from at least one of aluminum oxide, silicon dioxide, zirconium oxide, titanium dioxide, magnesium oxide, calcium oxide, zinc oxide, silicon nitride, silicon carbide and carbon materials; Preferably, the specific surface area of ​​the catalyst carrier is 25-190m 2 / g; Preferably, the pore volume of the catalyst carrier is 0.2-0.65 mL / g; Preferably, the average mechanical strength of the catalyst carrier is 20-100 N / mm; Preferably, the particle diameter of the catalyst carrier is 3-20 mm, preferably 3.5-17 mm; Preferably, the particle mechanical strength dispersion coefficient of the catalyst carrier is in the range of 0-0.

55.

3. A method for preparing a catalyst carrier, characterized in that: The method comprises the following steps: The carrier precursor is mixed with a peptizing agent and a modification aid, and then molded, dried and calcined to obtain a catalyst carrier; Wherein, the temperature change of the material before and after molding is less than 20°C; The modification aid is selected from at least one of compounds containing alkali metal elements, alkaline earth metal elements and rare earth metal elements.

4. The preparation method according to claim 3, wherein The temperature change of the material before and after molding is less than 18°C; Preferably, the mixing comprises dry blending, kneading and / or milling; Preferably, the kneading and / or mixing conditions include: the kneading and / or mixing time is 5-180 min, preferably 20-160 min; Preferably, the molding conditions include: a molding temperature of 1-60°C, preferably 5-50°C; a molding pressure of 3-20MPa, preferably 4-15MPa; Preferably, after adding the modification aid, a process of adding water is further included. Based on the weight of the carrier precursor being 1 g, the volume of water added is 0.5-1.5 mL, preferably 0.65-1.2 mL.

5. The preparation method according to claim 3 or 4, wherein The carrier precursor is a substance that is converted into a carrier by subsequent calcination; Preferably, the carrier is selected from at least one of alumina, silica, zirconium oxide, titanium dioxide, magnesium oxide, calcium oxide, zinc oxide, silicon nitride, silicon carbide, and carbon materials; Preferably, the carrier precursor is selected from at least one of pseudo-boehmite, calcium oxide and magnesium oxide; Preferably, the peptizing agent is an organic acid and / or an inorganic acid, preferably at least one selected from nitric acid, aluminum nitrate, acetic acid and citric acid; Preferably, relative to 100 parts by weight of the carrier precursor, the added amount of the peptizing agent is 0.4-10 parts by weight, preferably 0.6-8 parts by weight.

6. The preparation method according to any one of claims 3 to 5, wherein: The modification aid is selected from at least one of oxides, acetates, nitrates, hydroxides, carbonates and basic carbonates of alkali metal elements, alkaline earth metal elements, transition metal elements and rare earth metal elements; Preferably, the modification aid is selected from at least one of lanthanum nitrate, magnesium nitrate, zinc nitrate, potassium nitrate, magnesium oxide, calcium oxide, lanthanum acetate and magnesium acetate; Preferably, relative to 100 parts by weight of the carrier precursor, the amount of the modification aid added is 0.6-15 parts by weight, preferably 0.8-12 parts by weight.

7. The preparation method according to any one of claims 3 to 6, wherein: The mixing also includes adding an optional extrusion aid, an optional binder, and an optional lubricant; Preferably, relative to 100 parts by weight of the carrier precursor, the amount of the extrusion aid added is 0-8 parts by weight, preferably 0-6 parts by weight; Preferably, the amount of the binder added is 0-4 parts by weight, preferably 0-3 parts by weight, relative to 100 parts by weight of the carrier precursor; Preferably, the lubricant is selected from at least one of glycerol, polyol, polyester, magnesium stearate, stearic acid, talc and graphite; Preferably, relative to 100 parts by weight of the carrier precursor, the added amount of the lubricant is 0-10 parts by weight, preferably 0-5 parts by weight.

8. The preparation method according to any one of claims 3 to 7, wherein: The molding is selected from at least one of extrusion molding, compression molding and ball rolling molding; Preferably, the calcination conditions include: a calcination temperature of 700-1350°C, preferably 750-1250°C; a calcination time of 1-8 hours, preferably 2-6 hours; a heating rate of 1-8°C / min, preferably 2-6°C / min.

9. A catalyst carrier obtained by the preparation method according to any one of claims 3 to 8.

10. Use of the catalyst carrier according to any one of claims 1 to 2 and 9 in the field of catalyst preparation.

Citation Information

Patent Citations

  • High-performance catalyst carrier and preparation method thereof

    CN103480432A

  • Carrier and preparation method thereof, Fischer-Tropsch synthesis catalyst and Fischer-Tropsch synthetic method

    CN109382082A

  • Ruthenium-based catalyst and preparation method thereof, and Fischer-Tropsch synthetic method

    CN109382096A

  • Carrier, supported catalyst, preparation methods and applications of carrier and supported catalyst, and method for preparing synthetic gas by dry reforming of methane

    CN109718763A

  • Hydrofining catalyst as well as preparation method and application thereof

    CN116020481A